Case report: A novel SON mutation in a Colombian patient with ZTTK syndrome - Vasquez-Forero, Diana Marcela; Masotto, Barbara; Ferrer-Avargues, Rosario; Moya, Christian Martin; Pachajoa, Harry (Frontiers in Genetics, 2023)
Zhu-Tokita-Takenouchi-Kim (ZTTK) syndrome is a multisystem disorder caused by haploinsufficiency in the SON gene; characterized by developmental delay/intellectual disability, seizures, facial dysmorphism, short stature, and congenital malformations mainly in the central nervous system, along with ophthalmic, dental, pulmonary, cardiologic, renal, gastrointestinal, and musculoskeletal anomalies. Here we described the first Colombian patient with ZTTK with a novel mutation not previously reported and reviewed the clinical and molecular presentation of the patients described in the literature.